Advances in the role of resveratrol and its mechanism of action in common gynecological tumors - Yang, Qian; Meng, Dandan; Zhang, Qingchen; Wang, Jin (Frontiers in Pharmacology, 2024)
The incidence of common gynecological malignancies remains high, with current treatments facing multiple limitations and adverse effects. Thus, continuing the search for safe and effective oncologic treatment strategies continues. Resveratrol (RES), a natural non-flavonoid polyphenolic compound, is widely found in various plants and fruits, such as grapes, Reynoutria japonica Houtt., peanuts, and berries. RES possesses diverse biological properties, including neuroprotective, antitumor, anti-inflammatory, and osteoporosis inhibition effects. Notably, RES is broadly applicable in antitumor therapy, particularly for treating gynecological tumors (cervical, endometrial, and ovarian carcinomas). RES exerts antitumor effects by promoting tumor cell apoptosis, inhibiting cell proliferation, invasion, and metastasis, regulating tumor cell autophagy, and enhancing the efficacy of antitumor drugs while minimizing their toxic side effects. However, comprehensive reviews on the role of RES in combating gynecological tumors and its mechanisms of action are lacking. This review aims to fill this gap by examining the RES antitumor mechanisms of action in gynecological tumors, providing valuable insights for clinical treatment.